2021
DOI: 10.1002/ange.202106518
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Pd0‐ and PdII‐Catalyzed Cyclizations: Enantioselective Heck and Nucleopalladation Reactions

Abstract: An enantioselective consecutive cyclization/coupling process, catalyzed by palladium is reported. Stereoinduction arises from an enantioselective carbopalladation, generating an intermediate which promotes a nucleopalladation step. The dual cyclization sequence was compatible with a variety of alkyne-tethered oxygen-and nitrogen-centered nucleophiles, and a variety of alkenyl-tethered aryl iodides, to forge numerous bisheterocycles in good yields and high regio-and enantioselectivities.Scheme 1. Previous examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…In 2021, the Lautens group established a highly efficient palladium-catalyzed asymmetric cascade reaction of aryl halides with o-aminophenylenes, thereby offering the synthetically useful optically active diheterocyclic compounds in excellent yields with excellent regioselectivity and enantioselectivity (Scheme 55). [76] It is worth noting that different substituted phenylethynyl compounds and a series of aryl iodides with chain olefins were compatible with this protocol.…”
Section: Heck/cacchi Reactionmentioning
confidence: 94%
“…In 2021, the Lautens group established a highly efficient palladium-catalyzed asymmetric cascade reaction of aryl halides with o-aminophenylenes, thereby offering the synthetically useful optically active diheterocyclic compounds in excellent yields with excellent regioselectivity and enantioselectivity (Scheme 55). [76] It is worth noting that different substituted phenylethynyl compounds and a series of aryl iodides with chain olefins were compatible with this protocol.…”
Section: Heck/cacchi Reactionmentioning
confidence: 94%
“…7 Notably, Yao and co-workers have developed a palladium-catalyzed arylation/isoquinolinylation reaction of aryl iodides with 2-(1-alkynyl)benzaldimines for the preparation of 4-alkylated isoquinolines (Scheme 1a). 8 Later, elegant examples of synthesizing bisheterocyclic compounds through cascade Heck/nucleopalladation of alkene-tethered aryl halides with o-ethynyl anilines/phenols were reported by the groups of Lautens, 9 Chen, 10 and Lin (Scheme 1b). 11 Very recently, Wu and co-workers reported a palladium-catalyzed cascade cyclization reaction of aryl iodides with alkynyl oxime ethers (Scheme 1c).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Zhu synthesized atropoisomerically enriched bis-heterocycles through a Cacchi/Suzuki reaction cascade . Our group has reported the interception of both alkyl- and vinyl-Pd­(II) species to enantio- and stereoselectively synthesize linked bis-heterocycles (Scheme A). , With the goal of accessing novel heterocyclic scaffolds, we sought to merge Pd(0) and Pd­(II) catalysis.…”
mentioning
confidence: 99%
“…We began our investigation by subjecting compounds 1a and 2a (1.5 equiv) under similar reaction conditions to those in previous reports. , Pd­(PPh 3 ) 4 (10 mol %) and K 2 CO 3 (2.0 equiv) in MeCN at 100 °C led to the desired product 3a in 78% yield (Table , entry 1). Screening solvents revealed that THF was optimal for product yield and minimized the amount of 2-arylindole, arising from protodemetalation of 2a (entries 2–4).…”
mentioning
confidence: 99%